Caracterização do tecido fibroso de tururi e avaliação de propriedades mecânicas de compósitos de matriz poliéster reforçados com tecido fibroso de tururi - SANTOS, Avener Gleidson Andrade (Universidade Federal do Pará, 2023)
In recent decades, the search for materials with high mechanical performance and that are in accordance with sustainability requirements has become increasing. In the context of sustainability, the United Nations (UN) established in 2015 the Sustainable Development Goals (SDGs), in order to guide the paths to sustainable development. The use of waste to produce new materials is beneficial, because the use of these materials represents a solution for environmentally friendly disposal, thus covering the requirements established by the SDGs. The use of natural fibers in the production of new materials has increased significantly in the last decade. The use of natural fibers as reinforcement in polymer matrix composites is already well established. This is due to the fact that some fibers have high mechanical performance and good thermal stability, two highly attractive properties in composite materials. Composites reinforced with natural fibers have a vast field of application, and can be used in civil construction, aerospace, and automotive industries, among others. In this scenario, the use of tururi fabric as a reinforcement agent in composites of polymeric matrix emerges as a viable alternative for sustainable disposal of this waste coming from the harvesting stage of its fruits. Thus, this study aims to characterize the tururi fibrous tissue by optical microscopy, scanning electron microscopy, X-ray diffraction, thermogravimetric analysis and Fourier transform infrared spectroscopy (FTIR), as well as to determine physical properties such as density, moisture content and weight. The composites were produced using a 2.5, 5.0 and 7.5% by mass percentage of reinforcement. Additionally, tensile, flexural and charpy impact tests were performed. The characterizations revealed that the tururi fibrous tissue is composed of fibers of various diameters and has regions of bifurcation, indicating that the tissue can act in different ways when incorporated as reinforcement. The density, moisture content and weight had average values of 1.17 g/cm3, 16.58% and 146.61 g/m2, respectively. The thermal analysis revealed good thermal stability for the tururi fabric. The mechanical tests pointed out that as the incorporation of reinforcement occurred, the composites tested in traction had a loss of resistance, presenting a loss of 15MPa in relation to the matrix. When requested in flexion the composites reinforced with up to 2.5% showed better mechanical performance, with values of 63.9 MPa. The impact test revealed that the energy absorption capacity increased by 371% compared to the matrix, which indicates that the fabric acted as a good reinforcement agent.